Airway management considerations in patients with vocal fold implants - Shehata, Islam Mohammad; Masood, Waniyah; Daebis, Ahmad; Gamal, Islam; Urits, Ivan; Viswanath, Omar; Cornett, Elyse M.; Kaye, Alan D. (Frontiers in Anesthesiology, 2023)
Vocal fold implants (VFI) are used to manage glottis insufficiency, restore proper vocal cord functioning, and prevent aspiration. Implants with different physical properties are made from various materials. Patients with VFI present challenging airways. Perioperative physicians should recognize several considerations when confronting airway management in the setting of VFI. A preoperative assessment of patients with a VFI by a multidisciplinary team specialized in airway management is crucial. The best-fitting endotracheal tube and intubation technique can minimize the risk of implant displacement. The present investigation provides different options for airway management in the setting of VFI and describes solutions for special situations such as lung isolation and difficult intubation. An algorithm is presented as a visual tool to help anesthesiologists who encounter such patients for safe airway management while preserving the VFI.